Lens‐coupled folded‐dipole antennas for terahertz detection and imaging. Issue 11 (1st August 2015) - Rahman, Syed M.; Jiang, Zhenguo; Xing, Huili (Grace); Fay, Patrick; Liu, Lei
Abstract : The authors report the design, simulation and characterisation of lens‐coupled folded‐dipole antennas (LC‐FDAs) for terahertz (THz) detection and focal‐plane imaging arrays. LC‐FDAs operating at 200 GHz have been designed on semi‐insulating silicon wafers with a resistivity larger than 20 000 Ω·cm. Even–odd mode analysis (EOA) has been performed to extract the currents of the two modes. The embedding impedance of the designed LC‐FDAs has been simulated using conventional numerical electromagnetics, and the results show that a wide range of impedance values (both real and imaginary parts) can be achieved by changing the antenna geometry. This property makes LC‐FDAs suitable for high‐performance THz detectors in which impedance matching between antennas and devices is desired. From the currents calculated using EOA, the LC‐FDA far‐field radiation patterns, antenna directivity and Gaussian coupling efficiency for different lens structures have been examined using ray‐tracing techniques. Good agreement between calculation results and measurement has been observed demonstrating the effectiveness of the above analysis approach. The single element FDA design has also been explored for use in high‐resolution two‐dimensional THz focal plane arrays by optimising the lens structure and evaluating the off‐axis radiation patterns.